Building curriculum from the bottom: documenting a curriculum proposal in the context of COVID-19 - Cárdenas Alarcón, Constanza (2021)
The changes that school systems and societies due to COVID-19 were faced moving from an exceptionality of emergency to a situation where the emergency become the general rule. The present work describes an experience of curriculum construction developed by the education workers of the first cycle of primary school in a Chilean school. The process of participatory curriculum construction was based on the proposal of the generating themes of Paulo Freire, where the processes of construction of the content of the study programs are based on a theme and / or a problem of relevance to the educational community and to the interests of the students.